Bio-Engineered Wound Dressings: Unveiling Synergistic Healing Mechanisms through Computational Analysis - Veerabahu, Subbukutti; Janarthanan, Uma Devi Kumba (Scientific Research, New Technologies and Applications Vol. 9, 2024)
The wound dressing material plays a vital role in healing wounds and protecting the wound from infections. A wound dressing material was synthesized using bio-composites of chicken fibrin, fish scale collagen, spider web, and ethanolic leaf extract of Mangifera indica (L.). The synthesized biomaterial was analyzed through GC-MS. This study focuses on identifying bioactive compounds from the biosynthetic wound dressing material that may promote wound healing. The biological activities of the compounds were predicted using PASS online software, which helped explore their potential mechanisms in wound healing. PASS can predict over 4,000 different types of biological activities, including pharmacological effects, mechanisms of action, toxicity, metabolism, gene expression modulation, and the involvement of transporters. Ten bioactive compounds were identified as wound healing agents: 2-methyl-4-heptanol, 3-methoxy hexane, Stigmasterol, Z-3,17-octadecadien-1-ol acetate, 3-chloro-5-cholestene, 9,12,15-octadecatrienoic acid 2,3-bis(acetyloxy) propyl ester (Z,Z,Z), trans-Z-alpha-bisabolene epoxide, beta-carotene, Nopyl acetate, and 9,12-octadecadienoic acid (Z,Z) phenylmethyl ester. These compounds were analyzed and found to exhibit wound-healing mechanisms. By utilizing natural products, this innovative approach not only promotes effective wound healing but also aligns with the principles of sustainability and environmental stewardship.